Seasonality and life cycle of the jellyfish Lychnorhiza lucerna Haeckel, 1880 (Scyphozoa) in southern Brazil - ANDRESSA LEITE DA SILVA; CHARRID RESGALLA JR. (Anais da Academia Brasileira de Ciências)
Abstract Lychnorhiza lucerna, is a species of Scyphozoa with tropical and subtropical distribution in the western Atlantic. The knowledge of its life cycle is fragmented, with little understanding of environmental factors affecting growth processes and reproduction. This study evaluated the different phases of the life cycle of this macromedusa based on laboratory experiments with the polyp phase at different temperatures and 10 years of field data for the medusoid phase. Experiments on the polypoid phase determined a longer development time for the polyp population, highlighting the upward thermal shock for the excystment of podocysts and that the higher temperature (25 °C) stimulates greater production of ephyrae. In the south of Brazil, the presence of juveniles (< 5 cm in diameter) and adults (> 15 cm) of the medusoid phase was observed in winter and spring and during the period of upward variation in water temperature (18.5 to 23.8 ° C). These results confirm the annual life cycle of the species, that sporadic outbreaks (blooms) can be influenced by the stimulus of polyp strobilation. Based on the growth rates obtained in the laboratory and the population dynamics, this suggests that the organisms could be transported to the mouth of the Plata.